Too much job control? Two studies on curvilinear relations between job control and eldercare workers’ well-being - Kubicek, Bettina; Korunka, Christian; Tement, Sara (International journal of nursing studies)
Longer life expectancy and changes in family patterns in Western societies have increased the need for professional caregivers to the elderly. A detailed understanding of job resources, especially of job control, may help preserve eldercare workers’ work-related well-being. The aim of the present study was to determine optimal levels of job control for eldercare workers’ work-related well-being. Cross-sectional (Study 1) and longitudinal (Study 2) data were used to assess the linear and non-linear relations between job control and eldercare workers’ work-related well-being. As indicators of well-being, irritation was examined cross-sectionally, whereas burnout and engagement were used in the longitudinal study. In both studies, demographic variables and time pressure were included as controls. In Study 2, results were additionally controlled for baseline levels of the outcome variables. Study participants were recruited from the nursing staff of 10 publicly financed nursing homes for the elderly (Study 1) and from 18 privately and 20 publicly financed nursing homes for the elderly (Study 2). In both studies, eldercare workers (i.e., registered nurses, orderlies, and nursing assistants) were invited to answer paper–pencil questionnaires. In Study 1, 606 persons followed this invitation (response rate: 65%). In Study 2, 591 persons provided data on both measurement points (response rate: 35% of Time 1 participants). The samples of both studies were predominantly female and between 20 and 65 years of age. Hierarchical multiple regressions with linear and quadratic terms were conducted. Curvilinear effects of job control were found in both studies. In Study 1, low as well as high levels of job control were associated with higher levels of irritation compared to medium levels of job control. The longitudinal data from Study 2 supported these results. Eldercare workers with higher and lower levels of job control reported a higher tendency to depersonalize care recipients and a lower tendency to feel dedicated to, absorbed by and vigorous at work than those with medium levels of job control. Higher levels of job control are not necessarily advantageous for work-related well-being of eldercare workers.